Non-invasive and invasive diagnoses of aspergillosis in a rat model by mass spectrometry - Luptáková, Dominika; Pluháček, Tomáš; Petřík, Miloš; Novák, Jiří; Palyzová, Andrea; Sokolová, Lucie; Škríba, Anton; Šedivá, Blanka; Lemr, Karel; Havlíček, Vladimír (Scientific reports, 2017)
Invasive pulmonary aspergillosis results in 450,000 deaths per year and complicates cancer chemotherapy, transplantations and the treatment of other immunosuppressed patients. Using a rat model of experimental aspergillosis, the fungal siderophores ferricrocin and triacetylfusarinine C were identified as markers of aspergillosis and quantified in urine, serum and lung tissues. Biomarkers were analyzed by matrix-assisted laser desorption ionization (MALDI) and electrospray ionization mass spectrometry using a 12T SolariX Fourier transform ion cyclotron resonance (FTICR) mass spectrometer. The limits of detection of the ferri-forms of triacetylfusarinine C and ferricrocin in the rat serum were 0.28 and 0.36 ng/mL, respectively. In the rat urine the respective limits of detection achieved 0.02 and 0.03 ng/mL. In the sera of infected animals, triacetylfusarinine C was not detected but ferricrocin concentration fluctuated in the 3-32 ng/mL range. Notably, the mean concentrations of triacetylfusarinine C and ferricrocin in the rat urine were 0.37 and 0.63 μg/mL, respectively. The MALDI FTICR mass spectrometry imaging illustrated the actual microbial ferricrocin distribution in the lung tissues and resolved the false-positive results obtained by the light microscopy and histological staining. Ferricrocin and triacetylfusarinine C detection in urine represents an innovative non-invasive indication of Aspergillus infection in a host.
Keywords: Chromatography, Liquid; Humans; Mass Spectrometry; Metabolomics; Lung; metabolomika; krysa rodu Rattus; lidé; Biomarkers; zvířata; Colony Count, Microbial; plíce; Histocytochemistry; Aspergillosis; Invasive Pulmonary Aspergillosis; biologické markery; chromatografie kapalinová; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Siderophores; počet mikrobiálních kolonií; invazivní plicní aspergilóza; Rats; siderofory; Animals; histocytochemie; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Disease Models, Animal; hmotnostní spektrometrie; Aspergillus; aspergilóza; modely nemocí na zvířatech